Mechanical and fire performance of aluminium hydroxide filled E-Glass/phenolic hybrid composites. (2021) - Santhosh, M.S.; Thangavel, T.; Sasikumar, R.; Samsudeen, A.; Shahzada, Samshad; Sanjay, V.; kannan, C. Sai
Abstract: Nowadays probes stressing the progress of the phenolic matrix Glass Fiber Reinforced Plastics (GFRP) incorporated with fire retardant additive for the purpose of utilizing its supremacy on fire resistance and dimensional instability. In this research three specimens were obtained by distinct fire retardant additive (Aluminium Hydroxide) proportions and attributes. The desired samples produced by hand layup method were subjected to various tests namely flexural, Impact, tensile and UL94 tests etc. The outcomes of the tests reveal that the addition of additives strengthens composite structure and greatly enhances heat resistance and contracts the possibilities of occurrence of fire. Homogenously the fabricated glass fiber composite added with additives exhibits substantial resistance towards heat and humidity than the pure glass fiber composites. The final outcome of invented glass fiber composite is highly suggestible for the aerospace, defense, electric vehicles and storage tanks where sizable temperature is involved.